PENGEMBANGAN MEDIA BUKBAR (BUKU BERGAMBAR) BERBASIS KEARIFAN LOKAL LOMBOK UNTUK SISWA KELAS IV SDN GERUNUNG TAHUN AJARAN 2020/2021 - Handre Rizkiawan; Baiq Niswatul Khair; Nurul Kemala Dewi (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2022)
The purpose of this research is develop the Bukbar Media (Picture Book) based on Lombok Local Wisdom for grade IV Elementary School students. This research method uses 4-D (define, design, develop, and disseminate). The results of the study were the material validators got average score of 92.7, the media validators got average score of 92.86, the class teacher response validators and subject teachers got 81.36 and 93.69, the 6 students response validators got 86.50 in average. The criteria for assessing the media used in schools are in a good category for the media being developed.